Portugal: Von der linken Mehrheit zur »Zwinker-Regierung« (2015–2020) - Freire, A. (Left Diversity zwischen Tradition und Zukunft: Linke Parteienprojekte in Europa und ihre Potenziale, 2021)
The minority government of the PS, supported by three written agreements for a majority of leftists (PS) , with the BE, left-bloc – a left libertarian party -, the PCP, communists, and the PEV, greens, a communist satellite that always went to the pools in a joint list with the communists , which in governed throughout the XIII Legislature, in Portugal, raised since its inception many reservations, especially among its detractors. And it also had very low expectations of success and durability, even among its first-hour supporters. However, the reservations formulated proved to be unfounded and the performance of the government, and of the leftwing parliamentary majority, exceeded all expectations. After the 13th Parliamentary Term (XIII Legislature) and with new general elections held on 6 October 2019, which have already begun the 14th Parliamentary Term (XIV Legislature), a review of the record left-wing government and the parliamentary majority is required, as well as a preliminary analysis of its successor in the 14th Legislature, herein after the 'Blinker Government' (Governo Pisca-Pisca, in Portuguese: either blinks to the left or blinks to the right). It is worth studying the left-wing governmental alliance in Portugal for several reasons . First, because it can offer a solution for the social democratic parties in deep crisis in Europe (caused to largely by their convergence with the neoliberal agenda) pushing them back to the left (see Freire, 2021, forthcoming). Second, because it can offer to the radical left more influence in policymaking. Third, because this was a rare solution in a contemporary Europe where large coalitions and/or rainbow alliances (with or without social democratic involvement) were the norm. Fourth, because the Portuguese left-wing alliance has been quite successful in political and economic terms, producing political stability, GDP growth, lower unemployment, etc. (see Freire, 2021, forthcoming, for further details). Fifth, despite the reversal of austerity policies, the so-called leftwing government alliance complied with the EU economic and financial rules. Sixth, the growing interest that the Portuguese solution has received at national and international level from journalists and left-wing politicians from other countries who have come to see what was happening and take home some inspiration.